Investment Decisions in the Interbank Money Market Based on Islamic Principles - Rifki Ismail, Iwan Wisandani, Sri Iswati, Moslich Anshori, (Opción, 2019)
This study aims to investigate investment decisions in the interbank money market based on Islamic principles via a qualitative method with the type of phenomenological research. As a result, the most influential factors on manager behavior in investment decision making, including economic determinants, psychological determinants, social environmental determinants, determinants of organizational culture and ethos determinants of Islamic work. It can be concluded that the behavior of current treasury managers is not in line with the expectation of using monetary instruments rather than interbank money market instruments based on sharia principles so that the market is not deep.